Overcoming Barriers for siRNA Therapeutics: From Bench to Bedside - Muhammad Imran Sajid; Muhammad Moazzam; Shun Kato; Kayley Yeseom Cho; Rakesh Kumar Tiwari (MDPI AG, 2020)
The RNA interference (RNAi) pathway possesses immense potential in silencing any gene in human cells. Small interfering RNA (siRNA) can efficiently trigger RNAi silencing of specific genes. FDA Approval of siRNA therapeutics in recent years garnered a new hope in siRNA therapeutics. However, their therapeutic use is limited by several challenges. siRNAs, being negatively charged, are membrane-impermeable and highly unstable in the systemic circulation. In this review, we have comprehensively discussed the extracellular barriers, including enzymatic degradation of siRNAs by serum endonucleases and RNAases, rapid renal clearance, membrane impermeability, and activation of the immune system. Besides, we have thoroughly described the intracellular barriers such as endosomal trap and off-target effects of siRNAs. Moreover, we have reported most of the strategies and techniques in overcoming these barriers, followed by critical comments in translating these molecules from bench to bedside.